2006
DOI: 10.1097/01.cad.0000203379.14738.d9
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between methotrexate serum level and histologic response in the pre-operative treatment of extremity osteosarcoma

Abstract: Our objectives were to evaluate the behavior of different doses of pre-operative methotrexate (MTX) pharmacokinetics, and assess correlations between the osteosarcoma histologic response and MTX serum peak concentrations. In total, 336 patients with osteosarcoma of the extremities were treated with three neoadjuvant protocols of chemotherapy including high-dose MTX (different doses for each protocol), cisplatin and doxorubicin (same doses in all protocols). The doses of MTX were 8 g/m2 in 124 patients, 10 g/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Here, as well, the low sample size would explain the discrepancies with Tunn/Reichardt other studies [30]. Bacci et al [31] showed that an increasing dose of MTX increases the MTX serum peaks, but does not correlate with the histologic response of the tumor. Furthermore, Crews et al [32] proved that very high MTX exposures were associated with a poor outcome.…”
Section: Discussioncontrasting
confidence: 51%
“…Here, as well, the low sample size would explain the discrepancies with Tunn/Reichardt other studies [30]. Bacci et al [31] showed that an increasing dose of MTX increases the MTX serum peaks, but does not correlate with the histologic response of the tumor. Furthermore, Crews et al [32] proved that very high MTX exposures were associated with a poor outcome.…”
Section: Discussioncontrasting
confidence: 51%
“…Several studies have demonstrated that the response to HD-MTX is correlated with the delivered dose and the serum level of MTX, thus stressing the need for developing adaptivedosing methods [3,4,6,21]. Our institute has developed over the past decade Bayesian, dynamic adaptive dosing with feedback methods, which can be applied to various anticancer drugs such as CDDP, CBDCA, etoposide and MTX [11,[22][23][24].…”
Section: Discussionmentioning
confidence: 98%
“…Wide inter- and intra-variability in serum methotrexate levels has been observed following high-dose methotrexate (8–12 g/m 2 ) 19 . Higher serum methotrexate levels have been linked with better survival 20,21 but results have been inconsistent, with others finding no difference or even poorer survival, with peak concentrations >1500 μM 22 .…”
Section: Discussionmentioning
confidence: 99%